Unraveling the genetic architecture of stripe rust resistance in ICARDA spring wheat - Shewabez, Elias; Mugnai, Laura; Tadesse, Wuletaw; Alemu, Admas (Elsevier, 2025)
Stripe rust, also known as yellow rust, caused by Puccinia striiformis f. sp. tritici (Pst), is among the most destructive fungal diseases affecting global wheat productivity. Identifying genetic loci associated with Pst resistance is crucial for developing durable Pst-resistant wheat varieties. This study aimed to discover genetic markers linked to Pst-resistance in wheat using a 15 K single-nucleotide polymorphism (SNP) array. Field screenings were conducted over two years (2018 and 2019) on a panel of 245 wheat breeding lines developed by the International Center for Agricultural Research in the Dry Areas (ICARDA) at the Kulumsa Agricultural Research Center in Ethiopia. Importantly, 36 breeding lines exhibited consistent immunity or resistance across both growing seasons. Genome-wide association studies (GWAS) identified 34 marker-trait associations (MTAs) across 10 loci that surpassed the significance threshold. Half of these SNP markers were located on chromosome 7B, while the remaining were distributed across chromosomes 1B, 2B, 4B, 5 A, and 6B. Many identified quantitative trait loci (QTLs) were in close proximity to known Pst resistance genes/QTLs, suggesting they correspond to the same genetic regions. Additionally, three QTLs—EWYY5A.2, EWYY6B.1, and EWYY7B.3—were notably distant from any of previously identified Pst resistance genes, emerging as potential novel loci from this study. These QTLs represent promising candidates for marker-assisted selection, facilitating the development of wheat cultivars with enhanced resistance to Pst. Additionally, this study recommends incorporating the 36 consistently resistant lines into national and international wheat breeding programs to enhance Pst disease management efforts.